Knowledge Analysis with Coitus behavior In Pregnant Women in the First Trimester at BPM Rosa Siskawati, Plosoklaten District, Kediri Regency - Erma Retnaningtyas; Maria Febiola Lena; Asri Dewi Wahyuningtyas; Siti Kholisah (Journal of Health Science Community, 2023)
Until now, sexual issues are still considered taboo. But sex is a need. If one need is not met, it will cause psychological disorders for both the pregnant woman and her partner. Or it can even cause a breakdown in household relationships. The purpose of this research is to find out the relationship between knowledge and Coitus behavior In Pregnant Women in the First Trimester at BPM Rosa Siskawati, Plosoklaten District, Kediri Regency. The design of this research is a correlational research approach cross sectional. Respondents are recruited using techniques Purposive Sampling who meet the inclusion and exclusion criteria. The population studied was all pregnant women in the first trimester with a sample of 30 mothers. The Independent Variable studied is Knowledge and the Dependent Variable is Coitus behavior In First Trimester Pregnant Women. The results were analyzed using statistical tests Spearman Rank. The research results showed that knowledge of pregnant women in the first trimester was known to almost all respondents in the Good category, 23 (77%) respondents. Behavior Coitus For pregnant women in the first trimester, it was found that the majority of respondents were in the mild category, 19 (63%) respondents. The results of data analysis show that the significance level is 0.000 < α = 0.05 so that H0 is rejected and H1 is accepted thus there is a Relationship between Knowledge and Behavior Coitus In Pregnant Women in the First Trimester at BPM Rosa Siskawati, Plosoklaten District, Kediri Regency. Based on the research results, it is hoped that mothers should actively seek information about the dangers of having sexual intercourse during pregnancy and be able to find out the risks to the development of the fetus in the womb if the frequency of intercourse is irregular and even if the position of intercourse is uncomfortable.